2011
DOI: 10.1037/2157-3883.1.s.68
|View full text |Cite
|
Sign up to set email alerts
|

Work/Family Demands, Work Flexibility, Work/Family Conflict, and Their Consequences at Work: A National Probability Sample in Taiwan

Abstract: The aim of this research was to explore relations between work/family demands, work flexibility, work/family conflict, and work-related outcomes in the cultural context of Chinese society, using a national probability sample. For Taiwanese employees, work demands were positively related to work/family conflict, whereas both work and family demands were positively related to family/work conflict. Work/family conflict was negatively related to job satisfaction and family/work conflict to organizational commitmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 39 publications
2
28
0
2
Order By: Relevance
“…In this case, flexible management applications that allow employees to spend less time at work should be introduced. Lu et al [16] find that flexibility has a consistently positive effect for work outcomes, but an exacerbating effect for feelings that family life interfered with work.…”
Section: Relationship Between Motivation and Flexible Working Systemsmentioning
confidence: 99%
“…In this case, flexible management applications that allow employees to spend less time at work should be introduced. Lu et al [16] find that flexibility has a consistently positive effect for work outcomes, but an exacerbating effect for feelings that family life interfered with work.…”
Section: Relationship Between Motivation and Flexible Working Systemsmentioning
confidence: 99%
“…shift, rotation on weekends/holidays, and job transfer), their study predicts that Taiwanese correctional officers may experience work-family conflict, which in turn could negatively affect their job satisfaction. While, Lu et al (2008) found that organizational policies and practices such as work flexibility could alleviate feelings of work interfering with family, further enhancing job satisfaction and organizational commitment.…”
Section: Link Between Occupational Stress and Job Satisfactionmentioning
confidence: 99%
“…There have been researches into the relationship between work-family conflict and job satisfaction. Most studies have found a negative relationship between occupational stress and job satisfaction (Lambert et al, 2002;Lu et al, 2008;Calvo-Salguero et al, 2010;Chen et al, 2012). Lambert et al (2002) studied found that time-based work-to-family conflict negatively affects job satisfaction.…”
Section: Link Between Occupational Stress and Job Satisfactionmentioning
confidence: 99%
“…Numerous studies have shown that such conflicts accompany decreased satisfaction with both work and marriage, weaker perceived and procured social support, professional burnout, a greater amount of absenteeism at work and high level of stress, mental and physical ailments, and alcohol abuse [7,9,[11][12][13][14][15][16][17][18][19][20][21]. A meta-analysis of 60 studies on workfamily and family-work conflict performed by Byron [18] also shows that these conflicts are related to the intensity of fa mily and occupational stress.…”
Section: Introductionmentioning
confidence: 99%